Assessing the Relative Importance of Price, Safety, Energy Efficiency, Brand Reputation, and Warranty in Car Selection using SMART Method as Decision Support System - Mochammad Anshori; Jimmy Moedjahedy; Samuel PD Anantadjaya; Susi Indriyani; Ardimansyah Ardimansyah (JINAV: Journal of Information and Visualization, 2022)
The Simple Multi Attribute Rating Technique (SMART) is a decision support system that is widely used for evaluating and comparing alternatives based on multiple criteria. In this study, we applied the SMART method to assess the relative importance of price, safety, energy efficiency, brand reputation, and warranty in car selection. We assigned scores to each car model for each criterion, weighted the criteria based on their relative importance, and calculated an overall score for each car model. The results of this study show that the SMART method is a simple and easy-to-use tool that can help in making informed decisions in car selection. The method allows for the inclusion of both quantitative and qualitative criteria, making it versatile and applicable to a wide range of decision-making problems. Future research could focus on developing methods to address the limitations of the SMART method. Another area of research could be to integrate the SMART method with other decision-making tools, such as multi-criteria decision analysis or artificial intelligence, to improve its performance and applicability. Additionally, more research could be done on how to effectively use SMART method in real-life scenarios where the data is uncertain, incomplete and inconsistent